Workshop Pembuatan Alat Peraga IPA Bagi Alumni Program Studi Pendidikan IPA UNM - Salma Samputri; Rifda Nur Hikmahwati Arif; Ramlawati Ramlawati; Sitti Rahma Yunus; St. Mutia Alfiyanti Muhiddin (Program Studi Pendidikan IPA Fakultas MIPA Universitas Negeri Makassar, 2023)
One way that teachers can achieve learning success in training students to be independent and able to think creatively is by developing learning media that is suitable for application in the new curriculum. Learning media in the form of teaching aids can improve students' ability to understand the concept of the material because students can directly observe the processes that occur in it so that they can improve learning outcomes. However, most alumni of the science education study program still find it difficult to develop learning media for science teaching aids. This occurs due to the lack of experience and skills of alumni of the science education study program in implementing and making science teaching aids. Therefore, a training or workshop on making science teaching aids was held for alumni of the UNM Science Education Study Program.